789 Obstructive Sleep Apnea (OSA) and Vestibular Dysfunction in Patients with Traumatic Brain Injury (TBI). (3rd May 2021) - Skop, Karen; Bajor, Laura; Swank, Chad; Sevigny, Mitch; Tallavajhula, Sudha; Nakase-Richardson, Risa; Miles, Shannon
Abstract: Introduction: Recent work has highlighted prevalent OSA after TBI. Vestibular dysfunction is also common and associated with adverse outcomes particularly in military personnel. Vestibular dysfunction has been identified in patients with moderate to severe OSA, yet the relationship remains unexplored in those with TBI. This study examined the relationship of vestibular dysfunction with OSA in a large cohort of Veterans and Military Service Members (V/SM) with documented TBI. Methods: Data are secondary analyses from a five-center prospective observational cohort study of V/SM admitted for inpatient rehabilitation for TBI and enrolled in the VA TBI Model Systems. Participants completing study measures from 2015 to March of 2020 were included in analyses. Study measures includes the Centers for Disease and Control's National Health and Nutrition Education Survey (NHANES, OSA item embedded) epidemiologic survey and Neurobehavioral Symptom Inventory (NSI). T-tests and chi-square tests compared patients with OSA to those without OSA on the vestibular subscale on the NSI. Results: The sample was mostly male (93%), a mean of 38 years of age, and predominantly with mild (52%) or severe (41%) TBI. OSA was reported in 30.6% on the NHANES. Vestibular symptoms were more common among those with OSA (24%) compared to those without (12%) with a significant difference on the NSI Vestibular Total Score (3.84 vs 2.88 respectively; p<0.001). Similar results were seen across all three NSI vestibular items (dizziness, balance difficulties, poor coordination). Conclusion: Participants with TBI and comorbid OSA are more likely to endorse the presence and greater severity of vestibular symptoms compared to those without OSA. Future research is needed to improve understanding of the inter-relationship of OSA and vestibular dysfunction to inform clinical management. Support (if any): VA TBIMS & TBICoE (HT0014-19-C-0004), NIDILRR, North Texas TBI Model System (Grant #90DPTB0013), TIRR TBIMS (Grant #90DPTB0016)